Effects of Computerized Cognitive Training and Tai Chi on Cognitive Performance in Older Adults With Traumatic Brain Injury. Issue 3 (May 2020) - Hwang, Hei-Fen; Chen, Chih-Yi; Wei, Li; Chen, Sy-Jou; Yu, Wen-Yu; Lin, Mau-Roung
Abstract : Objective: To compare the effects of computerized cognitive training (CCT) and tai chi (TC) with usual care (UC) on cognitive functions and secondary outcomes in older adults with traumatic brain injury. Participants and Settings: Ninety-six patients aged 55 years and older who had a diagnosis of traumatic brain injury requiring hospital admission. Design: Randomized controlled trial. Main Measures: The Mattis Dementia Rating Scale (MDRS), Mini-Mental State Examination, modified Telephone Interview of Cognitive Status, and Trail Making Tests A and B. Results: Compared with UC, CCT increased scores on the MDRS's total, attention, and memory and those on the Mini-Mental State Examination and Telephone Interview of Cognitive Status over the 6-month intervention; TC increased scores on the MDRS's total and conceptualization and those on the Mini-Mental State Examination over the 6-month intervention, while it also increased scores on the MDRS's total and initiation/preservation and those on the Telephone Interview of Cognitive Status and reduced the time to complete the Trail Making Test B over the 12-month study. Furthermore, compared with UC, CCT increased handgrip strength and TC reduced the time to complete 5 sit-to-stands over the 6-month intervention. Conclusion: Both CCT and TC may improve global cognition and different specific cognitive domains in older traumatic brain injury patients; the TC's effect may last for at least an additional 6 months.